Sistem Pendingin Adsorpsi Double Bed Adsorber Dengan Laju Aliran Pendinginan Pada Evaporator 1 Kg/Min Pasangan Karbon Aktif-Metanol Sebagai Adsorben-Adsorbat - Pipin Azrin; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This paper presents the adsorption cooling system of double bed adsorberwith a working pairsactivated carbonmethanolas adsorbent-adsorbate that has a cooling capacity of 5000 BTU/hr-. This study is conducted experimental approach to investigate flow rate of cooling to the evaporatorof 1 kg/min.This studyaimed to know thetemperature of water comes out of from evaporator when the adsorption process. Cycle timewas given to the process of adsorption of 35 minutes and desorption of 50 minutes. Retrieval of data of the water temperaturecomes out of from evaporator using a thermometer ST-2 that was performed every5 minutes forpressure data retrievalfrom the pressure gauge.Process of adsorption cooling system of double bed adsorber through the process of adsorption (cooling, adsorption, and evaporation) and desorption (heating, desorption, and evaporation).In this studyalso aimed to generates COP (Coefficient of Performance) from the system. In this study resulted the lowest water temperature out of from evaporator of 26.2 °C, pressure of -60 cmHgwith evaporatorwater inlet temperature of 29.2 °C at time of 5 minutes adsorption processadsorber1.So the waterΔtwas 3 °C. COP generated by the system was 0.05214.Keywords: Adsorption, Desorption, COP (Coefficient Of Performance), Activated Carbon, Methanol